Study on the somato-functional changes of the junior female gymnasts aged 12 to15 years - Forminte, V. N.; Micu, R.; Grosu, E. F. (Science, Movement & Health, 2020)
Objective. The aim of this study was to assess the level of the somato-functional development and to analyze the relationship between their indicators in junior female gymnasts aged 12 to 15 years. Methods. A number of 6 gymnasts of 12 to 15 years old (members of the Romanian junior team of women`s artistic gymnastics) participated in this study. The somato-functional data were collected from the individual data sheets of the gymnasts after the medical examination made in the National Institute of Sports Medicine focusing on the anthropometric data, functional explorations and correlation between the studied indicators. Results. The results of the anthropometric and functional indices of the junior female gymnasts aged 12 -15 years reveal changes of the means relative to the standard deviation and differences between tests of t -parametric test related to the significance threshold of p < 0.05 and correlative connectionsin initial testing between the functional indices in lying down position at the diastolic blood pressure (DBP) and the somatic indices (SI): SI2, R = -0.88, SI5, R = -0.85, SI6, R = -0.95, SI7, R = -0.96, SI8, R = -0.81 and between DBP in orthostatism and SI9, R = -0.87. As for the final testing, in lying down position at the diastolic blood pressure (DBP) and SI2, R = -0.82, SI5, R = -0.86, SI6, R = -0.92, SI7, R = -0.97 and SI8, R = -0.81and between SPBin lying down position and SI10, R = -0.84. Conclusions. It has been confirmed that the performance artistic gymnastics has an influence on the somato-functional changes of the junior female gymnasts aged 12 to15 years and that there are significant correlative connections between the studied indices.